ChemInform Abstract: [V12O30F4(H2O)2] 4‐: One‐Pot Synthesis and Characterization of a Novel Fluorinated Dodecavanadate. Issue 50 (16th December 2014) - Krivosudsky, Lukas; Schwendt, Peter; Gyepes, Robert; Filo, Juraj
Abstract (NMe4)4 [V12O30F4(H2O)2] ·9H2O is synthesized from V2O5 dissolved in a solution of NMe4OH (ice bath), followed by addition of H2O2 and HF solutions (4 °C, 6 d, 12% yield).